From othering to self-naming: A womanist reading of the black female characters of Alice Walker’s The color purple - AZON, Sènakpon Adelphe Fortuné (My University, 2021)
Through the fictional characters of Alice Walker’s The color purple, this paper analyzes the social condition of African American females and the silent, mostly unseen violence they are exposed to. It focuses on the tridimensional challenges these women face, othered by sex, race, and class, as a social category deprived of voice and agency. It uses the womanist theory for its analysis of the novel’s text and comes to the conclusion, following the dynamics of the female characters of the book, that a collectively sustained fight, fecundated by love and understanding, is the soundest way to liberate both oppressed and oppressors.
Keywords: Key-words: The color purple; womanism; violence on women; oppression; African American females